(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to:1- Detecting the psychological fitness of kindergarten students2- The differences in the relationship in psychological fitness among female kindergarten students according to the stage variable and according to the following null hypothesis:• There are no statistically significant differences at the level (0.5) between the averages of psychological fitness for the first, second, third and fourth stages.To achieve the objectives of the research, the two researchers selected the research community from three colleges, namely the College of Basic Education, Al-Mustansiriya University, the College of Education for Girls, University of Baghdad, and the College of Basic Education, Wasit University. Applying it to the main sample, and after statistically processing the data, the two researchers reached the following:1- The kindergarten students are characterized by psychological fitness.2- There are statistically significant differences in the relationship in psychological fitness among female students of kindergarten departments and in favor of the first stage.Based on the results of the research, the two researchers developed a number of proposals and recommendations.